Implementing the Independent Curriculum through Teaching Campus (Kampus Mengajar) 7: A Qualitative Study of School-Based Literacy Supports - Sutinah Dwi Ningsih; Santoso Santoso (Yayasan Darussalam Bengkulu, 2024)
This study evaluates how the Independent Curriculum was operationalized through the Kampus Mengajar 7 literacy initiative in a non-metropolitan lower secondary school (SMPN 06 Mukomuko, Bengkulu, Indonesia). Using a descriptive qualitative design (25 February–16 June 2024), we purposively engaged information-rich stakeholders (principal, teacher partners, and the Kampus Mengajar team) and implemented three mutually reinforcing components: library revitalization (cataloguing, relabelling, layout optimization), mentored reading during otherwise idle minutes, and classroom-adjacent reading corners. Data naturalistic observations, field notes, activity logs, photo evidence, and simple visit/borrowing records were inductively coded and thematically analyzed with constant comparison; trustworthiness was addressed via triangulation, analyst debriefs, member checking, thick description, and an audit trail. Results show increased frequency and purposiveness of library visits and book loans, more disciplined on-task reading during mentored sessions, and active use of proximate reading corners; enabling conditions included supportive leadership, curated digital resources from the Platform Merdeka Mengajar, and teacher collaboration through Kelompok Kerja Guru, while constraints involved irregular library staffing and uneven early-stage pedagogical confidence. The study concludes that an integrated space + scaffold bundle can rapidly convert unstructured time into sustained literacy practice under realistic resource constraints. Schools should institutionalize a protected daily reading slot, assign minimal staffing or a teacher rota for library access, leverage Merdeka Mengajar exemplars to standardize lesson micro-structures, and protect PLC/KKG time; policymakers can pair digital provisioning with micro-grants and simple monitoring (visit/loan logs, pulse checks) to sustain routines, while future research should test durability and learning gains via multi-site, longitudinal designs with standardized literacy outcomes